RADI-03. ASL PERFUSION IMAGING OF THE FRONTAL LOBES PREDICTS THE OCCURRENCE AND RESOLUTION OF POSTERIOR FOSSA SYNDROME. Issue 2 (22nd June 2018) - Yecies, Derek; Shpanskaya, Katie; Grant, Gerald; Cheshier, Samuel; Hong, David; Edwards, Michael; Yeom, Kristen
Abstract: INTRODUCTION: Posterior fossa syndrome (PFS) is a common complication following the resection of posterior fossa tumors in children. The pathophysiology of PFS remains incompletely elucidated, however the wide-ranging symptoms of PFS suggest the possibility of wide-spread cortical dysfunction. In this study, we utilize arterial spin labeling (ASL), an MR perfusion modality that provides quantitative measurements of cerebral blood flow without the use of intravenous contrast, to assess cortical blood flow in patients with PFS. METHODS: A database of pediatric brain tumor patients treated at Stanford from 2004-2016 was retrospectively reviewed and 15 patients with PFS were identified. Immediate postoperative ASL for patients with PFS and age-matched medulloblastoma patients who did not develop PFS were compared. Additionally, in patients with PFS, ASL following the return of speech was compared with immediate postoperative ASL. RESULTS: On immediate postoperative ASL, patients who subsequently developed PFS had statistically significant decreases in right frontal lobe perfusion and a trend towards decreased perfusion in the left frontal lobe compared to controls. Patients with PFS had statistically significant increases in bilateral frontal lobe perfusion after the resolution of symptoms compared to their immediate postoperative imaging. CONCLUSION: ASL perfusion imaging identifies decreased frontal lobe blood flow as a strong physiologic correlate of PFS that is consistent with the symptomatology of PFS. This is the first study to demonstrate that decreases in frontal lobe perfusion are present in the immediate postoperative period and resolve with the resolution of symptoms, suggesting a physiologic explanation for the transient symptoms of PFS.